2022
DOI: 10.1111/1759-7714.14766
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel anoikis‐related gene signature to predict prognosis and tumor microenvironment in lung adenocarcinoma

Abstract: Background Lung adenocarcinoma (LUAD) is the most prevalent histotype of non‐small cell lung cancer. Anoikis, an alternative form of programmed cell death, plays a pivotal role in cancer invasion and metastasis, preventing the detached cancer cells from readhering to other substrates for abnormal proliferation. The aim of this study was to conduct a comprehensive analyses of the prognostic implications of anoikis‐related genes (ARGs) in LUAD. Methods ARGs were selected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…However, prognostic indicators based on ARGs have rarely been analyzed in LUAD. There was similar article has been published recently (17), however,our study could be more comprehensive because we not only constructed prediction risk model but also established two variously subtypes with "ConsensusClusterPlus" package and the clinical features and biological pathway in the two subtypes were also detected. In this study, we aimed to investigate the molecular alterations and clinical relevance of ARGs in LUAD, and to discuss the relationship between ARGs and LUAD prognosis, we found anoikis could regulate the immune function and metabolism procession which played great roles in prognosis in LUAD.…”
Section: Introductionmentioning
confidence: 91%
“…However, prognostic indicators based on ARGs have rarely been analyzed in LUAD. There was similar article has been published recently (17), however,our study could be more comprehensive because we not only constructed prediction risk model but also established two variously subtypes with "ConsensusClusterPlus" package and the clinical features and biological pathway in the two subtypes were also detected. In this study, we aimed to investigate the molecular alterations and clinical relevance of ARGs in LUAD, and to discuss the relationship between ARGs and LUAD prognosis, we found anoikis could regulate the immune function and metabolism procession which played great roles in prognosis in LUAD.…”
Section: Introductionmentioning
confidence: 91%
“…We obtained Anoikis-related genes from Diao et al 14 Univariate Cox analysis was conducted on Anoikis-related genes and key genes with prognostic effect were screened out ( p < 0.05). A resampling-based clustering method termed consistency clustering was applied in the TCGA-BLCA cohort using the ConsensusClusterPlus R package.…”
Section: Consistent Clustering Analysismentioning
confidence: 99%
“…Therefore, anoikis may play a crucial role in the occurrence and development of IS. Many studies have shown that anoikis is involved in the pathogenesis of several diseases, especially tumor immunity, such as glioblastoma ( Sun et al, 2022 ), head and neck squamous cell carcinoma ( Chi et al, 2022a ) and lung adenocarcinoma ( Diao et al, 2022 ). Despite growing evidence shows that anoikis regulates immune response, which plays a key role in the development of IS.…”
Section: Introductionmentioning
confidence: 99%